2022
DOI: 10.3390/ijerph19042128
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Safety of Prenatal and Neonatal Exposure to Paracetamol: A Systematic Review

Abstract: Introduction: Paracetamol is the most commonly used antipyretic and analgesic in pregnancy. It is also increasingly used off-label in the neonatal intensive care unit. Despite the frequent use of paracetamol, concerns have been raised regarding the high variability in neonatal dosing regimens and the long-term safety of early life exposure. Objective: To investigate the available evidence on the long-term safety of prenatal and neonatal paracetamol exposure. Methods: We conducted a systematic search of the ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…23 Prenatal exposure to acetaminophen is associated with an increased risk of neurodevelopmental, preeclampsia, atopic, and reproductive adverse outcomes. 24,25 In addition to cryptorchidism, acetaminophen and ibuprofen use during pregnancy has also been associated with hypospadias and cerebral palsy in children. 26 A cohort study suggested that ibuprofen may consider an analgesic and antipyretic of choice in the rst trimester.…”
Section: Discussionmentioning
confidence: 99%
“…23 Prenatal exposure to acetaminophen is associated with an increased risk of neurodevelopmental, preeclampsia, atopic, and reproductive adverse outcomes. 24,25 In addition to cryptorchidism, acetaminophen and ibuprofen use during pregnancy has also been associated with hypospadias and cerebral palsy in children. 26 A cohort study suggested that ibuprofen may consider an analgesic and antipyretic of choice in the rst trimester.…”
Section: Discussionmentioning
confidence: 99%
“…Although the median PNA of our population is 5 days, there are sufficient PCM observations to support the modeling and therefore dosing regimen until 30 days of PNA (71 PCM observations for PNA between 10–20 days and 52 observations for PNA between 20–30 days). It is important to note that the target concentration used in this study is based on limited efficacy and short-term safety studies in neonates [ 20 , 40 ], and there are still concerns regarding long term-safety of PCM for prenatal and neonatal use [ 41 ]. In addition, the high concentration of PCM-sulfate in the most immature neonates may be of concern, as studies have reported the depletion of sulfated sex hormones after using paracetamol [ 41 , 42 ].…”
Section: Disscussionmentioning
confidence: 99%
“…It is important to note that the target concentration used in this study is based on limited efficacy and short-term safety studies in neonates [ 20 , 40 ], and there are still concerns regarding long term-safety of PCM for prenatal and neonatal use [ 41 ]. In addition, the high concentration of PCM-sulfate in the most immature neonates may be of concern, as studies have reported the depletion of sulfated sex hormones after using paracetamol [ 41 , 42 ].…”
Section: Disscussionmentioning
confidence: 99%
“…Evidence points conclusively to the induction of autism spectrum disorder (ASD) with possible connections to both developmental delay and attention deficits [ 2 ]. Furthermore, evidence points toward exposure between birth and approximately 5 years of age as the period of highest risk, with the risk during prenatal exposure being significant in numerous studies [ 4 ] albeit less consequential [ 2 , 3 ]. Much of this evidence has recently been reviewed in detail elsewhere [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%